Comparison of elevated phosphorylated neurofilament heavy chains in serum and cerebrospinal fluid of patients with amyotrophic lateral sclerosis. Issue 4 (20th October 2017) - De Schaepdryver, Maxim; Jeromin, Andreas; Gille, Benjamin; Claeys, Kristl G; Herbst, Victor; Brix, Britta; Van Damme, Philip; Poesen, Koen
Abstract : Objective: Phosphorylated neurofilament heavy chain (pNfH) levels are elevated in cerebrospinal fluid (CSF) of patients with amyotrophic lateral sclerosis (ALS). Instead of CSF, we explored blood as an alternative source to measure pNfH in patients with ALS. Methods: In this single centre retrospective study, 85 patients with ALS, 215 disease controls (DC) and 31 ALS mimics were included. Individual serum pNfH concentrations were correlated with concentrations in CSF and with several clinical parameters. The performance characteristics of pNfH in CSF and serum of patients with ALS and controls were calculated and compared using receiver operating characteristic (ROC) curves. Results: CSF and serum pNfH concentrations in patients with ALS correlated well (r=0.652, p<0.0001) and were significantly increased compared with DC (p<0.0001) and ALS mimics (p<0.0001). CSF pNfH outperformed serum pNfH in discriminating patients with ALS from DC and ALS mimics (difference between area under the ROC curves: p=0.0001 and p=0.0005; respectively). Serum pNfH correlated inversely with symptom duration (r=−0.315, p=0.0033). CSF and serum pNfH were lower when the disease progression rate was slower (r=0.279, p<0.01 and r=0.289, p<0.01; respectively). Unlike CSF, serum pNfH did not correlate with the burden of clinical and electromyographic motor neuron dysfunction. Conclusions: CSF and serum pNfH concentrations are elevated in patients with ALS and correlate with the disease progression rate. Moreover, CSF pNfH correlates with the burden of motor neuron dysfunction. Our findings encourage further pursuit of CSF and serum pNfH concentrations in the diagnostic pathway of patients suspected to have ALS.